Resente Matteusnavorsing in Suid-Afrika - Combrink, H. J. B. (Hervormde teologiese studies, 1994)
Recent Matthean-research in South Africa This article deals with recent developments in Matthean research, mostly by members of the New Testament Society of South Africa. Initially, research on Matthew was influenced to a large degree by discourse analysis. Literary criticism and narratology also made an impact on this research, as well as speech-act theory, pragmatics and rhetoric. Social-scientific criticism also played a role, and the Sermon on the Mount has also been read as littérature engagée. Recently, the specific contribution of Matthew to the subjects of Theology and Ethics has also received attention. A growing sensitivity to the South African and the broader African context is also currently being seen..